Crisis, recovery, and gender identity in Iranian female participants of the Zār ritual "SHAMAN (Journal of the International Society for Academic Research on Shamanism) - Abbasi, Maryam (SHAMAN, 2019)
In southern Iran, the Zar ritual is a community-based activity which is used to treat people who are believed to be possessed by spirits. The most important spirit, called Zar, gives the possessed person a divine power in the eyes of others, in which she/he is allowed to ignore some social norms and enjoy societal respect without any punishment. From 2010 to 2016 I interviewed over fifty participants and non-participants in the Zar ritual and reviewed the literature in order to evaluate different aspects of the ritual. My fieldwork indicates that the Zar participants tend to be the most vulnerable and powerless members of society, who through their participation are able to avoid some of their gender-based predicaments and particular crises. The main research questions I sought to answer are: What are the predicaments and crises which lead women to turn to the Zar ritual for help? And how does participation in the Zar ritual facilitate their recovery? How do the women see this process?<br
Keywords: Ethnography; Esotericism; Anthropology of Dreams and Dreaming; Shamanism and Shamanic Healing